Teachers’ Perceptions and Instructional Practices toward Inclusive Education: Basis for a Strategic Training Program - Miraflor B. Agunod (Future Science / FSH-PH Publications, 2026)
Inclusive education has become a key priority in educational reform, promoting equitable access, participation, and learning opportunities for students with diverse educational needs. In the Philippines, national policies such as Republic Act No. 11650 mandate the provision of appropriate educational programs and support services for learners with disabilities within inclusive learning environments. This study assessed the perceptions and instructional practices of Special Education and General Education teachers regarding inclusive education in selected secondary schools in the Division of Naga City, Cebu, and examined the relationship between teachers’ attitudes and their competence in implementing inclusive practices. A quantitative descriptive–correlational research design was employed involving 20 teachers, comprising 10 Special Education and 10 General Education teachers. Data were gathered using adapted versions of the Multidimensional Attitudes toward Inclusive Education Scale (MATIES) and the Teacher Efficacy for Inclusive Practices (TEIP) Scale. Descriptive statistics and Pearson correlation analysis were used to analyze the data. Findings revealed that both Special Education and General Education teachers demonstrated moderately positive attitudes toward inclusive education (Special Education mean = 3.13; General Education mean = 3.11). Teachers also reported moderately high competence in inclusive teaching practices, including knowledge of inclusive strategies (Special Education mean = 3.46; General Education mean = 3.38), instructional skills for diverse learners (Special Education mean = 3.03; General Education mean = 3.10), and classroom management and assessment strategies (Special Education mean = 3.00; General Education mean = 3.10).